41-OR: Exploring the Role of Granulin in Sarcopenia—From Clinical Observations to Cellular Mechanisms - CHON CHAN, KA; HSUAN CHOU, YU; HSU, YUNG-HAN; WU, HUNG-TSUNG; OU, HORNG-YIH (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: Sarcopenia, characterized by the loss of skeletal muscle mass and function, is a significant complication of diabetes mellitus and is associated with increased hospitalization and mortality. Despite its clinical importance, the mechanisms underlying sarcopenia remain unclear. Granulin, derived from progranulin, has been implicated in muscle hypertrophy and the activation of the AKT/mTOR pathway. Therefore, we investigated the role of granulin in sarcopenia. Methods: A total of 172 subjects were enrolled, and the appendicular skeletal muscle mass index (ASMI) was measured. Serum granulin levels were measured by ELISA. To clarify the causal relationship between granulin and sarcopenia, high-fat diet and hindlimb ligation sarcopenic animal models were used. L6 myoblast cell line was used to investigate the possible mechanisms. Results: Serum granulin concentrations were significantly lower (280.71±148.09 ng/mL vs 378.96±139.65 ng/mL, p<0.001) in the low muscle mass group (n=30) compared to the normal group (n=142). Reduced muscle granulin expression was also observed in sarcopenic mice. In L6 cells, granulin enhances glucose uptake and protein synthesis through the AKT/mTOR pathway. Knockdown of Ephrin type-A receptor 2 (EphA2) gene abolished granulin's effects on glucose uptake and protein synthesis, indicating that EphA2 pathway is essential for mediating granulin's functions. Conclusion: Granulin regulates skeletal muscle mass and function, highlighting its potential as a biomarker and therapeutic target for sarcopenia.